Temperature differences associated with colour do not determine where the acorn ant Temnothorax crassispinus (Hymenoptera: Formicidae) chooses to nest - Sławomir MITRUS (Institute of Entomology, Biology Centre, Czech Academy of Science, 2021)
Temperature is an important factor for invertebrates. Social insects build nests, which along with their ability to thermoregulate, provide shelter from extreme temperatures. However, for many species of ants the most common method of controlling the temperature inside a nest is to choose a suitable nest site. During a field experiment, the choice of nest site by the acorn ant Temnothorax crassispinus, a species which lives in coniferous and mixed forests, was studied. It typically occupies ephemeral nest sites and can move to a new nest site several times in one season. It was predicted that in early spring, dark coloured nest sites would be warmer and thus more frequently occupied by ant colonies. Contrary to this prediction, no difference was recorded in the frequency with which dark and lighter coloured nests were occupied. However, also in contrast to the prediction, in forest in early spring the difference in temperature inside different coloured nests was small. Thus, other features of nests, e.g., volume of cavity, are probably more important in determining nest site selection by this ant.